Identification of Human Resource Planning Factors in In-house Construction Management (Owner-Managed Construction) Affecting the Time Performance of Hotel Development Projects - Rahma Ghaesani Subagja; Rully Andhika Karim (Greenation Research & Yayasan Global Resarch National, 2026)
In projects implementing an In-house Construction Management (CM) system, the effectiveness of human resource (HR) planning is a critical aspect in supporting the achievement of project time targets, particularly in projects whose Owners lack a construction-related background. This condition is commonly found in Hotel Development Projects, as the Owner's core business is neither in the construction sector nor in hotel operations. Therefore, this study aims to analyze the HR planning factors of In-house CM in owner-managed construction with limited project management background, and to examine their influence on project time performance. The study employs a descriptive quantitative approach using a case study method. Data were obtained through a literature review, expert validation to determine the level of influence of indicators on time performance, and the distribution of questionnaires to project respondents to identify the existing conditions. Data analysis was conducted using the Relative Importance Index (RII) method, mean score, and the Spearman correlation test. The RII results identified 12 indicators categorized as